PENGARUH KETINGGIAN DI ATAS TANAH DAN JARAK DARI EMPULUR TERHADAP BERAT JENIS DAN KADAR AIR KAYU AFRIKA (KHAYA ANTHOTHECA C.DC.) - Suparman Nurwati; Edi Sarwono (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
Khaya anthotheca C.DC. is one of exotic tree species selected for trial planting in Indonesia by the Forest Research Institute, about 25 years ago.This paper discusses the result of a laboratory study on the variation of wood moisture content and air dry specific gravity within and between trees, the effects of height from the ground and distance from pith outward on these two properties. The material for the study consisted of three 20 year old trees of Khaya anthotheca C.DC. with diameters at breast height ranging from 38 - 41 cm, height (until top) 15 - I 7 m and clear bole length from 9 - 9.5 meters. The trees were felled on plantation site at Cikole (North of Bandung) on the slope of Mount Tangkuban Perahu, and transported to Bogor for laboratory testing.The result of statistical analyses reveal, non significant differences between trees and bolts within trees for air dry specific gravity, and significant difference in the property from pith outward.The green (fresh) moisture contents on the other hand between bolts and distance from pith are significantly different. Regressions relating the two properties (air dry specific gravity and moisture content) as dependent variables with respective distance from pith outward being 1/3, 2/3, and 3/3 of the radius, and height of bolt 0.2, 2.7, 5.2, and 7.7 meters above the ground as independent variables show the following :(1).S = 0.436 - 0.017Z + 0.003 Z2 = (R=0.536) (Z =Height, S =Specific gravity)(2).A = 99.98 - 3.591Z + 0.224 Z2 = (R=0.466) (Z = Height, A = Moisture content)(3).S = 0.396 + 0.018 X + 0.044X2 = (R=0.510) (4).A= 86.79 - 1.495 x + 4.25X2 = (R=0.101) (X = distance from pith outward)Test of significance of the regression coeficient (Table 4) indicate significant F values for the first two equations (effect of height) and non significant results for the last two equations (effect of distance from pith).